2022
DOI: 10.3390/ijms23137386
|View full text |Cite
|
Sign up to set email alerts
|

BBX24 Interacts with DELLA to Regulate UV-B-Induced Photomorphogenesis in Arabidopsis thaliana

Abstract: Abstracts: UV-B radiation, sensed by the photoreceptor UVR8, induces signal transduction for plant photomorphogenesis [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…In simulated shade, BBX24 can sequester DELLA to promote elongation responses through PIF4 activity [23,24]. More recently, it has been suggested that the module of HY5-BBX24-DELLA can control the crosstalk between GA and UV-B signaling to regulate hypocotyl inhibition [21]. Together, our results suggest that BBX24 can promote seed germination in suboptimal stressful environments by integrating ABA and GA signals.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In simulated shade, BBX24 can sequester DELLA to promote elongation responses through PIF4 activity [23,24]. More recently, it has been suggested that the module of HY5-BBX24-DELLA can control the crosstalk between GA and UV-B signaling to regulate hypocotyl inhibition [21]. Together, our results suggest that BBX24 can promote seed germination in suboptimal stressful environments by integrating ABA and GA signals.…”
Section: Discussionsupporting
confidence: 56%
“…Several BBX proteins have been documented to be involved in seedling de-etiolation, synthesis of anthocyanins, shade avoidance, flowering and responses to abiotic and biotic stresses [13,16]. BBX24 has been documented to inhibit seedling deetiolation [17][18][19][20], repress UVB signaling [21,22] and promote shade avoidance [17,23,24] and flowering [25]. BBX24 was originally isolated as a SALT-TOLERANT (STO) protein in an Arabidopsis cDNA clone screen that conferred increased salt-tolerance in Saccharomyces cerevisiae [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about how BBX genes coordinate with genes from phytohormone signaling pathways to regulate UV-B-induced physiology and development in plants. AtBBX24 interacts with DELLA proteins in the GA pathway to regulate UV-B-induced photomorphogenesis in Arabidopsis [ 28 , 70 ]. We determined that 11 VcBBX s respond to UV-B radiation, and their expression was significantly correlated with that of many genes involved in phytohormone signaling pathways, especially the auxin, ethylene, and BR pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this is also the case for true leaves, is to our knowledge not reported. Other interaction partners include GAI‐ASSOCIATED FACTOR 1 (GAF1)/INDETERMINATE DOMAIN 2 (IDD2), with the double idd1 idd2 mutant showing a semi‐dwarf plant phenotype (Fukazawa et al., 2021), and ELONGATED HYPOCOTYL 5 (HY5), of which a loss‐of‐function hy5 mutation results in bigger cotyledons and first leaves (Huang et al., 2022; Sibout et al., 2006).…”
Section: Ga/della Pathwaymentioning
confidence: 99%